Intonation of Greek in contact with Turkish: A diachronic study - Baltazani, Mary; Przedlacka, Joanna; Ünal Logacev, Özlem; Logacev, Pavel; Coleman, John (Cambridge University Press, 2022)
Asia Minor Greek (AMG) speakers cohabited with Turkish speakers for eight hundred years until the 1923 Lausanne Convention, which forced a two-way mass population exchange between Turkey and Greece and severed their everyday contact. We compare the intonation of the continuation rise tune in the speech of first-generation AMG speakers born in Turkey with three subsequent generations born in Greece. We examine how long contact effects in intonation persist after contact has ceased, through comparison of the f0 patterns in four generations of AMG speakers with those of their Athenian Greek- and Turkish-speaking contemporaries. The speech of the first-generation of AMG speakers exhibits two patterns in the f0 curve shape and time alignment of the continuation rises, one Athenian-like and one Turkish-like. Over subsequent generations use of the latter diminishes, while the Athenian pattern becomes more frequent, indicating intergenerational change.
Keywords: Continuation Rise Tune; Curve Fitting; Diachronic Data; Intergenerational Change; Intonation